Chemical Methods for the Construction of Spirocyclic β-Lactams and Their Biological Importance - Yadav, Pooja; Berry, Shiwani; Bhalla, Aman (Synthesis, 2024)
Spirocyclic β-lactams are a family of natural and synthetic chemicals with different biological activities, including antibacterial properties, and interact with critical physiological targets such as T-type calcium channels and acetyl-CoA cholesterol acyltransferase. Their unique chemical structure, combining a spiro ring system with a β-lactam group, offers promising opportunities for the targeted discovery of medications in medicinal chemistry. Spirocyclic β-lactams have the potential to be adaptable frameworks for developing novel therapeutic medicines with particular three-dimensional pharmacophoric characteristics and increased biological efficacy. Numerous methods are employed for the synthesis of spirocyclic β-lactams, such as cyclization, functional group modifications, asymmetric synthesis utilizing chiral catalysts and biomimetic approaches. In this short review, two distinct approaches describing recent syntheses of spirocyclic β-lactams (from 2021 to 2024) are discussed. The first is based on constructing the β-lactam ring, while the other entails transforming monocyclic β-lactams into spirocyclic structures. These methods include detailed reaction processes and descriptions of the biological functions of the target spirocycles. The applications of spirocyclic β-lactams in medicinal chemistry highlight their role in the synthesis of structurally diverse compounds with significant therapeutic potential, demonstrating creative chemical methods for building complex molecular structures.1 Introduction2 β-Lactam Ring Synthesis3 Non-β-Lactam Ring Synthesis4 Miscellaneous Examples5 Conclusion and Outlook
Keywords: spirocyclic β-lactams; cycloaddition; cyclization; Cu catalysis; ketene formation; NHC-catalyzed annulation